Research on the impact of delayed retirement on the subjective wellbeing of older adults - Guan, Guo-feng; Wang, Lu; Ma, Dong-fen; Luo, Pan-shi (Frontiers in Public Health, 2025)
As China prepares to implement delayed retirement policies in response to population aging, understanding the impact of extended working lives on older adults' wellbeing has become increasingly important. While prior studies have focused on economic outcomes, less is known about the subjective consequences of working beyond traditional retirement age. This paper examines the effect of delayed retirement on the subjective wellbeing of older adults in China, with attention to underlying mechanisms and potential heterogeneity across gender and income groups. Using micro-level survey data from a period when delayed retirement was voluntary rather than mandatory, we identify the impact of retirement deferral on subjective wellbeing. We further explore three potential mechanisms and conduct subgroup analyses by gender and household income levels. We find that delayed retirement significantly increases subjective wellbeing among older adults. The improvement appears to result from enhanced social capital and a stronger sense of achievement, while reduced participation in intergenerational caregiving may partly offset the benefits. Gender heterogeneity analysis reveals that the positive effect is significant only for men, likely due to the additional domestic responsibilities faced by women. Similarly, income heterogeneity shows that benefits accrue primarily to higher-income individuals, whereas lower-income individuals experience no significant gains, possibly due to the involuntary nature of their extended work. These findings suggest that delayed retirement has complex effects on wellbeing, shaped by both social roles and economic constraints. Policy efforts should promote flexible and equitable retirement transitions, improve workplace support for older workers, and address the family-level tensions that may arise from extended employment.